Seed germination characteristics and control options for Noogoora bur (Xanthium strumarium) in commercial maize production - James, T.K.; Rahman, A.; Trolove, M.R.; Dowsett, C.A. (New Zealand Plant Protection, 2016)
Noogoora bur (Xanthium strumarium) is a large herbaceous highly competitive annual weed of arable and horticultural crops which is subject to Regional Pest Management Plans in the Waikato and Bay of Plenty regions New Zealand A study with scarified burs showed that most plants emerged from 040 mm and none from 100 mm depth Plants emerged after 8 days from 030 mm after 14 days from 90 mm and continued to emerge over summer with some also germinating in the second year after initiation Cultivated fallow resulted in germination of similar numbers of seeds over two growing seasons with no new seed input Results from a field trial showed that dicamba and atrazine alone or in combination with other products as well as topramezone provided good control of this weed in maize crop